Year-round and Migratory Birds of the Flint Hills - William H. Busby (Symphony in the Flint Hills, 2012)
The Flint Hills support a wide diversity of birds. with some 250 species having been recorded. They range in size from the Ruby-throated Hummingbird (3 grams) to the 10-kg Wild Turkey. Birds tend to specialize by habitat, and each habitat---be it tallgrass prairie, shrublands, riparian forest, cropland, or farmstead---supports its own assemblage of bird species.
Keywords: birds; season; migration; migratory; year-round; Flint Hills; Ruby-throated hummingbird; wild turkey; habitat; native; natural; nature; bird watching; shrublands; species; tallgrass; grassland; prairie; cropland; riparian forest; home; ecosystem; Dickcissel; Eskimo Curlews; songbird; Western Meadowlark; Grasshopper Sparrow; nests; nesting; short eared owl; egg; female; male; Loggerhead Shrike; Greater Prairie-Chicken; breeding